Uniaxial Tensile Simulation of 3D Orthogonal Woven Fabric - M.F, Yahya; S.A, Ghani; B, Zahid (International Journal of Engineering and Technology, 2018)
Mesoscale modelling approach has shown close simulation approximations of woven fabric tensile performance. The main purpose of the work is to develop understanding of geometrical model development, finite element analysis procedure and to compare the differences of 2D and 3D woven fabric uniaxial tensile stress-strain. 3D woven fabric structures selected for the work is three-layer orthogonal woven fabrics. The woven structure will have 2 through-thickness warps, 4 non-crimps warp and 6 wefts. Through-thickness warp yarn will apply plain 1/1 weave structure for stitching all weft layers and non-crimps weft yarn together. Woven geometric models were developed with pre-processor program at detail yarn configurations. Simulation results showed that 3D orthogonal woven fabric had a better tensile response than its 2D woven fabric structures.Â Â